A new exposure of the Dobrotiva Formation in the Praha-Vokovice area (Middle Ordovician) - Budil,P. (Journal of the Czech Geological Society, 1999)
From the classical palaeontological area in Praha-Vokovice a large section of the Dobrotiva Formation (Dobrotivian Stage) is described, exposed on the south bank of the 'Dzban' water reservoir. The area near Praha-Vokovice and Praha-Divoka Sarka, has been known as a geological locality, probably since 1845 (cf. Zippe 1845). As a palaeontological locality, it has been known since 1862-1863 (cf. Krejci 1863). Barrande (1872) described finds of the trilobite Placoparia zippei (Boeck) from 'les environs de Vokovitz, dans le vallon dit Sarka'. Palaeontological material from Barrande's collection from the localities 'Vokovitz' and 'Sarka' is deposited in the palaeontological collections of the National Museum, Prague, too. Most investigations in the Vokovice and Sarka area culminated in the 80s of the 19th century to the middle of the 20th century. During the 70s and 80s of the 20th century, most of the palaeontological localities in this area were destroyed due to building activities. The newly described section belongs to the last large Ordovician outcrops in this area. Lower to middle parts of the Dobrotiva Formation (Middle Ordovician, Dobrotivian stage) are exposed on this locality. This stratigraphical sequence is characterised by the alternation of horizons of light coloured sandy quartzites and dark, bituminous silt- and claystones. Lower and middle parts of Dobrotiva Formation are very fossiliferous in this area. The fauna and ichnofauna discovered in the section (more than 20 species and ichnospecies) come from siliceous nodules weathering from the siltstones and claystones. A monotonous association of the ichnofauna (Skolithos ichnofacies) is limited on the quartzites. A schematic profile through the section, brief characteristics of the six distinguished litho-intervals, notes on the tectonic structures, and faunal lists are presented.
Keywords: Middle Ordovician; Prague Basin; Dobrotiva Formation